КОНСТИТУЦІЙНИЙ ПРОЦЕС В УКРАЇНІ: У ПОШУКАХ ПОЛІТИЧНОГО І ПРАВОВОГО КОМПРОМІСУ - ТОМЕНКО, Микола Володимирович (SUPREMANCE OF LAW, 2016)
The paper presents the concept of «three legitimacies» of Constitution. It consists in the fact that for the successful approval of the constitution or constitutional amendments, the process of the new Basic Law passage must gain legitimacy in the legal, political and social fields.
Keywords: constitutionalism; constitution process; political risk; political compromise; political issues